The effect of prenatal cocaine exposure on the stress response of adult mice - Planeta, Cleopatra S. [UNESP] (2001)
The neurotoxic consequences of intrauterine exposure to drugs of abuse, including cocaine, may include compromised fetal brain development with associated lasting behavioral alterations. Some infants exposed to cocainein utero demonstrate impairments in reactivity and altered behavioral responses to stressful conditions. Alterations in arousal regulation can impact on socialization, adaptation, and educability. Moreover, such alterations may render cocaine-exposed children more vulnerable to the adverse developmental impact of stressful situations, with implications for subsequent behavior and psychopathology.Animal models facilitate the independent analysis and identification of genetic, intrauterine, and postnatal environmental factors in contributing to cocaine-induced alterations in behavioral and neurochemical responses to stressors. Utilizing a prenatal mouse model of gestational cocaine exposure we have identified a behavioral alteration evident as decreased duration of footshock-induced immobility termed freezing in cocaine-exposed adults as compared with controls. However, this attenuated behavioral response was not accompanied by demonstrable alterations in corticosterone response, nor was the corticosterone response altered in cocaine-exposed adults following a more protracted restraint-induced stress. The dissociation of these behavioral and neurochemical indices of altered response to stressors may provide insights regarding brain mechanisms underlying alterations in behavioral reactivity to stressful conditions followingin utero cocaine exposure. In addition, this preclinical study may have implications for improved diagnostics and therapeutics for infants and children exposed to cocaine in the womb.